Muscarinic receptor-mediated nitric oxide release in a K562 erythroleukaemia cell line - AYDIN OMAY, BANU; CABADAK, HÜLYA; GÖREN, MEHMET ZAFER (My University, 2009)
1 In the present study we have investigated the expression of muscarinic receptors in K562 erythroleukaemic cells and the effects of muscarinic agonist and antagonists on extracellular citrulline levels in these cells, as a marker of nitric oxide (NO) generation. 2 Muscarinic acetylcholine receptors (M 1-M5) play key roles in regulating many diverse physiological processes. Recent studies suggest that muscarinic receptors mediate some cellular events in haematopoietic cells. Multiple subtypes of muscarinic receptors are expressed in different human cells. NO, a free radical and a signaling molecule, is involved in the regulation of many physiological functions and derived from certain nitric oxide synthases (NOS), which are related to muscarinic receptors. 3 In this study, the presence of M2, M3 and M4 subtypes in K562, an erythroleukaemic cell line, was demonstrated by using the reverse transcriptase-polymerase chain reaction. Moreover, the generation of NO induced by carbachol, a non-selective muscarinic agonist, was investigated by using high-performance liquid chromatography to measure changes in extracellular l-citrulline levels. 4 We found that carbachol enhanced l-citrulline production in K562 erythroleukaemic cells. The effect of carbachol on l-citrulline production was antagonized by atropine and 4-diphenylacetoxy-N-methylpiperidine (4-DAMP), while tropicamide had little effect. These results suggest that the muscarinic receptor M 3 subtype may mediate NO signaling in K562 erythroleukaemic cells. © 2009 Blackwell Publishing Ltd.
Keywords: 4-DAMP; Arginine; Carbachol; Citrulline; NO; Tropicamide